Prediksi Epitop Sel B Berbasis Peptida Glikoprotein 160 sebagai Kandidat Vaksin Subunit untuk Infeksi Human Immunodeficiency Virus (HIV) - Amelia Putri Permata Sari; Dina Mulyanti; Budi Prabowo Soewondo (UNISBA Press, 2024)
Abstract. The Human Immunodeficiency Virus (HIV) epidemic is still a major threat to public health in the world, including Indonesia. HIV is a virus that infects white blood cells, especially CD4, so that the human immune system decreases. Currently, the treatment of HIV infection is by administering antiretroviral drugs (ARVs), although these drugs cannot eliminate all viruses from the patient's body. Vaccines are an effective effort to prevent infection, but until now there has been no vaccine for HIV that has been approved for use. This study aims to analyze the glycoprotein peptide 160 of the HIV virus that has the potential to be developed into a subunit vaccine in silico. A series of in silico analyses were carried out, including searching for conserved regions and ensuring that B cell epitopes as vaccine candidates can produce an immune response. This study produced 4 candidate epitopes for B cells based on surface accessibility and antigenicity values. The best epitope with a surface accessibility value of 3,516 and antigenicity of 1.07 is owned by the YLKDQQL epitope. This epitope is suspected of having the potential to be a candidate for an HIV vaccine. Abstrak. Epidemi Human Immunodeficiency Virus (HIV) masih menjadi ancaman besar bagi kesehatan masyarakat di dunia, salah satunya Indonesia. HIV merupakan virus yang menginfeksi sel-sel darah putih khususnya CD4, sehingga sistem kekebalan tubuh manusia menjadi menurun. Saat ini penanganan infeksi virus HIV adalah dengan pemberian obat antiretroviral (ARV), meskipun obat tersebut tidak dapat menghilangkan seluruh virus dari tubuh penderita. Vaksin merupakan upaya yang efektif untuk mencegah infeksi, tetapi hingga saat ini belum ditemukan vaksin untuk HIV yang berhasil disetujui penggunaannya. Penelitian ini bertujuan untuk menganalisis peptida glikoprotein 160 dari virus HIV yang berpotensi untuk dikembangkan menjadi vaksin subunit secara in silico. Serangkaian analisis in silico dilakukan, termasuk pencarian daerah lestari (conserved) dan memastikan epitop sel B sebagai kandidat vaksin dapat menghasilkan respon imun. Penelitian ini menghasilkan 4 kandidat epitop untuk sel B berdasarkan nilai aksesibilitas permukaan dan antigenisitas. Epitop terbaik dengan nilai aksesibilitas permukaan sebesar 3.516 dan antigenisitas sebesar 1.07 dimiliki oleh epitop YLKDQQL. Epitop tersebut diduga berpotensi sebagai kandidat vaksin HIV.